Neuroprotective Effect of Ginkgo biloba and L-Ascorbic Acid on Mercury Chloride (HgCl2)-Induced Oxidative stress and Neuroinflammation in Adult Male Wistar Rats (Biological Sciences, 2024)
Mercury chloride (HgCl2) toxicity poses significant health risks upon exposure. Chronic exposure can lead to severe neurological damage. Ginkgo biloba extract (EGB761) enhance cognitive function and memory. Ascorbic acid is a powerful antioxidant that helps protect cells from damage by free radicals. The present study evaluates the effects of EGB761 and L-Ascorbic Acid on HgCl2-Induced Oxidative Stress and Neuroinflammation. 48 adult Wistar rats were randomly divided into 6 groups of 8 rats each. The control group received distilled water. HgCl2 Only received (5 mg/kg HgCl2), HgCl2 + A. A received (5 mg/kg HgCl2 + 100 mg/kg A. A, HgCl2 + A. A received (5 mg/kg HgCl2 + 500 mg/kg A. A, HgCl2 + EGB761 received (5 mg/kg HgCl2 + 100 mg/kg EGB761, and HgCl2+ EGB761 received (5 mg/kg HgCl2 + 500 mg/kg EGB761. All administration was done orally for 21 days. The animals were subjected to a Y maze test and sacrificed on day 22. The brain was excised, and 1 g of tissue homogenized and utilized to assay for (MDA, SOD, CAT, GSH) and (TNF- α, and IL-6) activity. The result showed significant (p
Keywords: Ginkgo biloba; Mercury Chloride; Ascorbic acid; Oxidative stress; Neurotoxicity; Inflammation